(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
On the basis of the frequency of occurrence of bryophytes in Kharkiv region 60 species and varieties can be classified as rare, 73 as relatively rare and 75 as common species on this territory. The belonging to the class Sphagnopsida and the lack of sporophytes and vegetative propagules are positively associated with local rarity, while the belonging to pleurocarpous mosses, the growth form of mats, the monoicy and the sporophyte production are negatively associated. Up-to-date natural reserve fund provides protection of localities of 176 species, of which only 36 are locally rare. The habitats with high relative proportion of rare bryophyte species as sphagnum bogs and chalk outcrops are presented insufficiently in the NRF and their number should be increased.